The Effect of Stadium Atmosphere on the Satisfaction and Behavioral Intention of Spectators: New Eskişehir Stadium Case - Çevik, Hüseyin (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
The income obtained from the spectators who watch matches at the stadium is among the primary incomes of football teams. It is required to draw more spectators to the stadium in order to increase this income. The most important factor that motivates spectators to attend the match is the stadium atmosphere. Thus, it is considered that examining the effects of stadium atmosphere on the consumption behaviors of spectators is essential in terms of clubs and managers who desire to increase their match income. Therefore, in the present study, it was aimed to examine the effect of the stadium atmosphere on satisfaction and behavioral intention of spectators. The data were obtained by questionary from spectators who watch the matches in the New Eskisehir Stadium. "The Stadium Atmosphere Scale" was included in the first part of the survey, and items that measure satisfaction and behavioral intention were included in the second part. The structural equation model was used for data analysis. First, the measurement model was tested, and then the relationship between the structures was revealed with path analysis. The results of the study revealed that the stadium atmosphere has a positive and direct effect on both the satisfaction and behavioral intention of the spectators. In conclusion, the suggested model, which was based on the literature, provides essential information about the role of stadium atmosphere on the consumption behaviors of spectators to the football clubs and managers.